PENGARUH PEMBERIAN AKUPRESUR TERHADAP PENURUNAN EFEK SAMPING MUAL DAN MUNTAH PADA PASIEN TB PARU DENGAN PENGOBATAN OAT - Pratiwi, Chaterina Janes; Hariyono, Rudi; Wahyuni, Lutfi; Pujiwati, Ely (Coping: Community of Publishing in Nursing; Vol 12 No 1 (2024): Februari 2024DO - 10.24843/coping.2024.v12.i01.p06, 2024)
Patients with pulmonary TB infection who undergo Obat Anti Tuberkulosis (OAT) therapy generally experience the side effect of nausea and vomiting which can increase the high drop out rate at the start of treatment. Giving acupressure at points P6 and ST36 is believed to reduce the incidence of nausea and vomiting due to administration of OAT. Experimental research design with pre-post test design. The sampling technique used in this research is purposive sampling. There were 65 respondents involved in this research. Respondents were TB patients at Bangil Hospital, Pasuruan Regency, East Java. Acupressure therapy is provided by certified professionals. Nausea and vomiting were measured using the Rhodes Index Nausea Vomiting and Retching (RINVR). The level of nausea and vomiting before being given acupressure therapy was 31% of respondents with severe nausea, 42% of respondents with moderate nausea, and 26% of respondents with mild nausea. Meanwhile, the level of nausea and vomiting after acupressure therapy was 12% of respondents with moderate nausea, 80% of respondents with mild nausea and 8% of respondents with no nausea. The results of the Wilcoxon rank test with a p-value = 0,000 which means that statistically with a confidence level of 95% it is believed that there is an effect of giving acupressure on reducing the side effects of nausea and vomiting in pulmonary TB patients with OAT treatment. The more often acupressure intervention is given, the fewer complaints of nausea and vomiting.